Pronounced coronary artery calcification: Casual finding in transthoracic echocardiography - Konstandin, Mathias; Hardt, Stefan; Katus, Hugo; Mereles, Derliz (International journal of cardiology, 2011)
Echocardiographic finding of mitral annulus calcification and aortic sclerosis have been shown to be associated with higher incidence and prevalence of cardiovascular risk factors. Here, we report direct visualization of coronary artery disease of the LAD by non-invasive transthoracic echocardiography confirmed by coronary angiography. Further study is needed to evaluate septal calcification as a novel cardiovascular risk marker.
Available online 6 November 2009
Gesehen am 06.07.2022